2019
DOI: 10.1111/jcmm.14519
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatase activity of soluble epoxide hydrolase regulates ATP‐binding cassette transporter‐A1‐dependent cholesterol efflux

Abstract: The contribution of soluble epoxide hydrolase (sEH) to atherosclerosis has been well defined. However, less is understood about the role of sEH and its underlying mechanism in the cholesterol metabolism of macrophages. The expression of sEH protein was increased in atherosclerotic aortas of apolipoprotein E‐deficient mice, primarily in macrophage foam cells. Oxidized low‐density lipoprotein (oxLDL) increased sEH expression in macrophages. Genetic deletion of sEH (sEH−/−) in macrophages markedly exacerbated oxL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Beside the famous effect of EETs hydrolysis, sEH are also able to directly interact with proteins like Akt and AMP-activated protein kinase (AMPK) [ 10 , 20 , 21 ]. In this study, we revealed that sEH may be able to associate with Sirt3 under high Pi condition.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the famous effect of EETs hydrolysis, sEH are also able to directly interact with proteins like Akt and AMP-activated protein kinase (AMPK) [ 10 , 20 , 21 ]. In this study, we revealed that sEH may be able to associate with Sirt3 under high Pi condition.…”
Section: Discussionmentioning
confidence: 99%
“…1 a), which are other bioactive phospholipid mediators, to monoacylglycerol (MAGs) [8] , [9] , [10] , [11] . In addition, in vitro cellular works suggested a complementary role of sEH-H and sEH-P activities in the regulation of metabolic or vascular homeostasis [12] , [13] , [14] , [15] . While recombinant mice that do not express ephx2 have been around for some time [16] , [17] , they do not allow to specifically studying sEH-P because both activities are eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory response initiated by lipid-laden macrophages and the regulation of cholesterol metabolism is inevitable to the initiation and progression of AS (Lien et al, 2019). An increased macrophage cholesterol efflux was proven to significantly and inversely associate with cardiovascular diseases (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%